Reconstruction of Law Number 12 of 2022 Concerning Criminal Acts of Sexual Violence: The First Milestones in Eliminating Sexual Violence in Indonesia - Karso, A. Junaedi (LPPM Institut Pendidikan Nusantara Global, 2025)
The enactment of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence in harmony with Islam, as stated in the Qur'an, QS. An-Nur verse 33. Prohibiting violence against women also contradicts the values of monotheism, and Al-Insaniyah is a concrete manifestation and gift for women in Indonesia. It has very comprehensive content regulating the classification of criminal acts of sexual violence, physical sexual harassment, forced contraception, forced sterilization, forced marriage, sexual torture, sexual exploitation, sexual slavery, and electronic-based sexual violence. It establishes appropriate penalties and optimizes the prevention and handling of cases of sexual violence in Indonesia, which continues to show a high level every year. However, its implementation has not been as optimal as desired by victims and the public due to several obstacles, including: 1) Not all derivative regulations of the TPKS Law have been enacted; 2). Limited human resources, facilities, infrastructure, and operational costs, and only 30 percent of districts/cities in Indonesia have safe houses for victims of sexual violence.